Structure, gene regulation and environmental response of flagella in Vibrio - Zhu, Shiwei; Kojima, Seiji; Homma, Michio (Frontiers in Microbiology, 2013)
Vibrio species are Gram-negative, rod-shaped bacteria that live in aqueous environments. Several species, such as V. harveyi, V. alginotyticus, and V. splendidus, are associated with diseases in fish or shellfish. In addition, a few species, such as V. cholerae and V. parahaemolyticus, are risky for humans due to infections from eating raw shellfish infected with these bacteria or from exposure of wounds to the marine environment. Bacterial flagella are not essential to live in a culture medium. However, most Vibrio species are motile and have rotating flagella which allow them to move into favorable environments or to escape from unfavorable environments. This review summarizes recent studies about the flagellar structure, function, and regulation of Vibrio species, especially focused on the Na+-driven polar flagella that are principally responsible for motility and sensing the surrounding environment, and discusses the relationship between flagella and pathogenicity.